ANALISIS RETURN ON INVESTMENT (ROI) PROGRAM SERTIFIKASI PROFESIONAL SEBAGAI INSTRUMEN EVALUASI INVESTASI SDM DI BANK RAKYAT INDONESIA CABANG TUBAN - Nurul Fauziyah; Novi Vizainiyah; Anjar Sulistyowati; Ahmad Mudzakkir (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2026)
This study evaluates the Return on Investment (ROI) of two professional certification programs at Bank Rakyat Indonesia Tuban Branch—Teller Certification (STB) and Anti-Money Laundering/Counter-Financing of Terrorism (AML/CFT)—using the Phillips ROI Methodology. Employing a mixed-methods explanatory sequential design, quantitative data from 23 participants were analyzed through cost-benefit analysis, impact isolation, and monetary conversion, while qualitative insights identified intangible benefits. The results show a substantial difference in ROI, with STB achieving 492% and a 2.4-month payback period driven by cross-selling revenue and efficiency gains, whereas AML/CFT yielded 34% ROI with a 35.5-month payback period, mainly reflecting its role in risk mitigation and regulatory compliance. Despite lower financial returns, both programs contributed significant non-financial benefits such as enhanced professional authority, knowledge standardization, and employee retention. This study highlights the distinction between “value-creating” and “value-protecting” certifications, offering a strategic framework for optimizing human capital investments in the banking sector.